My life as polluted pond scum - Myers, Bill, 1953- (Nashville, Tenn. Tommy Nelson, 1996)
Thirteen-year-old Wally must learn to trust God when his Career Day assignment on the local water management facility leads him to a rumor of a lake monster and a real scheme that threatens the town.
4.8
3-6
3-6
780
Keywords: Pollution -- Fiction; Christian life -- Fiction; Humorous stories; Pollution -- Fiction; Christian fiction; Humorous fiction